The effect of a randomised controlled lifestyle intervention on weight loss and plasma proneurotensin - Louise Bennet; Ayesha Fawad; Joachim Struck; Sara Lönn Larsson; Andreas Bergmann; Olle Melander (BMC Endocrine Disorders, 2022)
Abstract Aims Proneurotensin (Pro-NT) is a strong predictor of cardiometabolic disease including type 2 diabetes and obesity, however, the effect of lifestyle change on Pro-NT has not been investigated in this context. Middle Eastern (ME) immigrants represent the largest and fastest growing minority population in Europe and are a high-risk population for obesity and type 2 diabetes. In this randomised controlled lifestyle intervention (RCT) addressing ME immigrants to Sweden where weight-loss was previously studied as the main outcome, as a secondary analysis we aimed to study change in Pro-NT during follow-up and if baseline Pro-NT predicted weight loss. Methods Immigrants from the Middle East at high risk for type 2 diabetes were invited to participate in this RCT adapted lifestyle intervention of four months’ duration. The intervention group (N = 48) received a culturally adapted lifestyle intervention comprising seven group sessions and a cooking class addressing healthier diet and increased physical activity. The control group (N = 44) received treatment as usual with information to improve lifestyle habits on their own. Data assessed using mixed effects regression. Outcomes Primary outcome; change in Pro-NT. Secondary outcome; change in BMI in relation to baseline plasma concentration of Pro-NT. Results During the four months follow up, weight was significantly reduced in the intervention (-2.5 kg) compared to the control group (0.8 kg) (β -0.12, 95% CI -0.24 to -0.01, P = 0.028). Pro-NT increased to a significantly greater extent in the intervention compared to the control group during follow up (28.2 vs. 3.5 pmol/L) (β 11.4; 4.8 to 18.02, P < 0.001). Change over time in BMI was associated with baseline Pro-NT (β 0.02; 0.01 to 0.04, P = 0.041). Conclusion In consistence with data from surgical weight loss, this RCT paradoxically shows increased levels of Pro-NT during a multifactorial lifestyle intervention resulting in weight loss. Long term studies of Pro-NT following weight loss are needed. Trial registration This study is a secondary analysis of the RCT trial registered at www.clinicaltrials.gov . Registration number: NCT01420198. Date of registration 19/08/2011. The performance and results of this trial conform to the CONSORT 2010 guidelines.